Body size from unconventional specimens: A 3D geometric morphometrics approach to fishes from Ancestral Pueblo Contexts. (June 2022) - Dombrosky, Jonathan; Turner, Thomas F.; Harris, Alexandra; Jones, Emily Lena
Abstract: Animal body size estimation from zooarchaeological specimens often relies on specific, one-dimensional (i.e., conventional) measures from skeletal elements. Here, we introduce an animal body size estimation technique for archaeological fishes that relies on 3D reference scans and the calculation of centroid size, a standard 3D geometric morphometric proxy measure for organism size. Centroid size-based estimations on whole caudal vertebrae are strongly correlated with a widely accepted measure (i.e., centrum width), but the scalability and flexibility of the centroid size-based approach allows for use on a wide variety of fragmented remains. We use zooarchaeological fish remains (subfamily Ictiobinae) from late pre-Hispanic period large village sites located in the Middle Rio Grande region of New Mexico. Informal reports suggest that fishes were large during this time, and we demonstrate that ictiobines were significantly large compared to modern specimens. The centroid size-based body size estimation technique indicates that Ancestral Pueblo fishing strategies were associated with energy maximizing foraging behavior. Highlights: A new body size reconstruction method is as reliable as common techniques. It answers questions about fishing strategies in difficult contexts. It is applied to fishes from sites in the Middle Rio Grande of New Mexico. Results suggest environmental change is linked to fishing in the Middle Rio Grande.